Design of a Drug Inventory Information System at Janji Primary Health Center Using a MySQL Database - PeZaitun Ritonga; Masrizal Masrizal; Rahma Muti’ah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This research is backgrounded by observation data at the Labuhanbatu appointment health center and uses the MYSQL database system to help support research results. MySQL is also known as a SQL-based open-source relational database management system (RDBMS) that works with a client-server model which functions for data warehousing (data warehouse), which is data collection from various sources, for e-commerce, as well as logging applications. Information systems are an important factor in Indonesia today, supporting operational activities and institutions for companies. An information system is an internal organizational system that meets the needs of day-to-day event management, supports operations, represents the specific management of the organization, and supports strategic operations with the necessary reports. The system design includes drug inventory, Primary Health Center Standards, and Drug Services. The research methods used are a combination of survey research, problem identification, data collection, data analysis, system design, and implementation. This research also aims to make more agencies know how to work quickly and easily using MYSQL databases, researchers hope that in this digital era people will know more and understand more about information systems and their uses to help in work.The result of this research is that the puskesmas is willing to consider the problems that arise from the current system, which is recommended to implement and utilize computerized systems that offer a more effective and efficient data search process. The proposed system is a modification of the ongoing system, namely the Design of the Drug Stock Information System at the Promise Health Center. This system design uses PHP, CSS, Bootstrap Designer, and MySQL. Therefore, the design results obtained include a program interface consisting of Files, Transactions, Reports, and Final Programs (Exit).